Hypogonadism alters cecal and fecal microbiota in male mice. (1st November 2016) - Harada, Naoki; Hanaoka, Ryo; Hanada, Kazuki; Izawa, Takeshi; Inui, Hiroshi; Yamaji, Ryoichi
ABSTRACT: Low testosterone levels increase the risk for cardiovascular disease in men and lead to shorter life spans. Our recent study showed that androgen deprivation via castration altered fecal microbiota and exacerbated risk factors for cardiovascular disease, including obesity, impaired fasting glucose, excess hepatic triglyceride accumulation, and thigh muscle weight loss only in high-fat diet (HFD)-fed male mice. However, when mice were administered antibiotics that disrupted the gut microbiota, castration did not increase cardiovascular risks or decrease the ratio of dried feces to food intake. Here, we show that changes in cecal microbiota ( e.g., an increased Firmicutes / Bacteroidetes ratio and number of Lactobacillus species) were consistent with changes in feces and that there was a decreased cecal content secondary to castration in HFD mice. Castration increased rectal body temperature and plasma adiponectin, irrespective of diet. Changes in the gut microbiome may provide novel insight into hypogonadism-induced cardiovascular diseases.